Kebertahanan Metode Hafalan Dalam Pembelajaran Bahasa Arab - Devi Suci Windariyah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2018)
Memory method is a classic learning method that has been used by the Arabs since Islam began to come. Until now this method is still often used in pesantren salaf and modern pesantren. IAIN Jember is the only Islamic state college located in the horseshoe. The development and progress in IAIN Jember has undergone some changes to the learning method used in Arabic learning along with the development of Arabic language learning innovation. But in fact there are some Arabic instructors who are still strongly maintaining to use the memorization method in Arabic learning. Even though it was a lot of contradictions from campus citizens.